The Role of Maternal Support in Developing Attitudes and Managing Anxiety of Adolescent Girls at Menarche: A Correlational Study - Hindrati, Yusmar Izza; Yulifah, Rita; Marcelina, Sheilla Tania (EMBRIO: Jurnal Kebidanan, 2024)
Menarche is the first menstrual period during adolescence, which experiences changes during menarche and experiences anxiety. This research aimed to determine the relationship between maternal support and the attitudes and anxiety of adolescent girls facing menarche in Kalirejo Bangil Village. The design research correlation analysis was done using a cross-sectional approach, with a sample size of 38 teenage girls in grades 4-6 who had menstruated at the Kalirejo Bangil State Elementary School using a proportional random sampling technique. This research instrument uses a questionnaire. The data analysis was univariate and bivariate with the Spearman rank correlation test. The results of the univariate analysis showed that 29 teenage girls (76.3percent) had sufficient maternal support, 30 adolescent girls (78.9percent) had a good attitude, and 24 teenage girls (63.2percent) experienced moderate anxiety in facing menarche. Based on the results of the analysis using the Spearman Rank, it was found that in the variable maternal support and the attitude of adolescent girls, the P-value was 0.342, which means there is no relationship between maternal support and the attitude of adolescent girls in facing menarche, while in the variable maternal support and adolescent girls' anxiety, the P-value was 0.017, which means there is relationship between maternal support and adolescent girls' anxiety in facing menarche. Maternal support did not directly influence adolescent girls' positive or negative attitudes. However, there is a significant relationship between maternal support and adolescent girls' anxiety levels. The higher the perceived support, the lower the level of anxiety experienced.